2021
DOI: 10.1016/j.jad.2020.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the contribution of the Big Five personality traits, health anxiety, and COVID-19 psychological distress to generalised anxiety and depressive symptoms during the COVID-19 pandemic

Abstract: Highlights First study to examine the contribution of the Big 5 personality traits, health anxiety, and COVID-19 psychological distress to generalised anxiety and depressive symptoms. COVID-19 psychological distress predicts generalised anxiety and depressive symptoms beyond all other variables. Specific personality traits appear to be protective of COVID-19 psychological distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

59
271
3
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 257 publications
(343 citation statements)
references
References 45 publications
(58 reference statements)
59
271
3
10
Order By: Relevance
“…It is important to point out that these effects were observed when controlling for other Big Five traits (i.e., conscientiousness, agreeableness, openness). Overall, these results are consistent with the differential reactivity model of personality and stress (Bolger & Zuckerman, 1995) and recent findings in the context of the COVID-19 pandemic, suggesting that both extraversion (Nikčević et al, 2020;Wijngaards et al, 2020) and emotional stability (Kocjan et al, 2020;Kroencke et al, 2020;Lee & Crunk, 2020;Liu et al, 2020;Pradhan et al, 2020) relate to general levels of perceived stress, mental health, and subjective wellbeing during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It is important to point out that these effects were observed when controlling for other Big Five traits (i.e., conscientiousness, agreeableness, openness). Overall, these results are consistent with the differential reactivity model of personality and stress (Bolger & Zuckerman, 1995) and recent findings in the context of the COVID-19 pandemic, suggesting that both extraversion (Nikčević et al, 2020;Wijngaards et al, 2020) and emotional stability (Kocjan et al, 2020;Kroencke et al, 2020;Lee & Crunk, 2020;Liu et al, 2020;Pradhan et al, 2020) relate to general levels of perceived stress, mental health, and subjective wellbeing during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, research shows that less emotionally stable people react more strongly to stressful events than more emotionally stable people (Bolger & Schilling, 2006). Consistently, recent cross-sectional studies found that emotional stability was positively related to resilience (Kocjan et al, 2020) and negatively related to perceived threat, STRESSFULNESS OF COVID-19 8 perceived stress, depressive symptoms, and anxiety during the COVID-19 pandemic (Lee & Crunk, 2020;Liu et al, 2020;Nikčević et al, 2020;Pradhan et al, 2020). Moreover, a largescale experience sampling study with over 38,000 momentary reports provided by 1,609 participants found that less emotionally stable individuals paid more attention to information related to the COVID-19 pandemic, worried more about the consequences of the pandemic, and experienced more negative affect during the pandemic (Kroencke et al, 2020).…”
Section: The Role Of Extraversion and Emotional Stabilitymentioning
confidence: 86%
See 1 more Smart Citation
“…One study by López-Núñez and colleagues found that individuals low in neuroticism but high in conscientiousness, extraversion, and agreeableness had better mental health in terms of anxiety, depression, and life satisfaction during the COVID-19 outbreak in Spain [ 20 ]. Similarly, Nikčević and colleagues (2020) found neuroticism, as well as openness to experience, to be associated with higher levels of COVID-19 anxiety among the general population in the United States [ 21 ]. Agreeableness, extraversion, and conscientiousness had an opposite effect [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Nikčević and colleagues (2020) found neuroticism, as well as openness to experience, to be associated with higher levels of COVID-19 anxiety among the general population in the United States [ 21 ]. Agreeableness, extraversion, and conscientiousness had an opposite effect [ 21 ]. In a study conducted among young adults in India, higher neuroticism was connected to higher levels of death anxiety in the wake of the 2020 pandemic; however, this relationship was fully mediated by perceived stress [ 22 ].…”
Section: Introductionmentioning
confidence: 99%